KERJASAMA INDONESIA – MALAYSIA DALAM MENANGANI TRANSBOUNDARY HAZE POLLUTION (STUDY KASUS: PROVINSI RIAU)TAHUN 2008 - Muhammad Azan; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study describes the cooperation between Indonesia and Malaysia in response totransboundary haze pollution in Riau Province in 2008. The purpose of this study is to determinehow the cooperation between Indonesia and Malaysia in response to transboundary hazepollution problem.The research method used is a descriptive of qualitative research method about the facts.This research is an explanatory that describe about problem, indication, policies, and actions. Inwriting techniques, the author’s collect and collate data through library research from severalsources like books, journals, articles, websites, the media and others. In this study also use theconcept of international cooperation.Forest fires result in the emergence of smog and haze pollution. The smog is not only feltby Indonesia alone, but other countries also feel the smog. One of the countries that feel thesmog is Malaysia.Malaysia agreed to cooperate with Indonesia to tackle land and forest fires inRiau Province, followed by the signing of the agreement mutual of understanding on 03 June2008 in Jakarta.Keyword: Indonesia and Malaysia Interest, Transboundary Haze Pollution.